Adhesive composition, optical component, electronic component, and electronic module
The adhesive composition, tailored with specific polymerizable compounds and thermosetting agents, addresses the limitations of conventional adhesives by enhancing adhesion, deep curing, and temporary fixation, thereby ensuring robust bonding in photothermal and photocuring applications.
Patent Information
- Application Number
- JP2020100278
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-09
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2040-06-09
AI Technical Summary
Conventional adhesive compositions used in photothermal curing and photocuring applications often experience issues such as peeling, displacement of moving parts, and poor storage stability due to curing shrinkage and lack of deep curing properties.
An adhesive composition comprising a polymerizable compound, a photopolymerization initiator, and a thermosetting agent, specifically formulated to achieve optimal adhesion, deep curing, and temporary fixation properties through precise control of the hard, intermediate, and soft segment ratios, as determined by pulsed NMR analysis.
The adhesive composition exhibits excellent adhesion during photothermal curing, deep curing properties, and temporary fixation capabilities, ensuring strong bonding and stability in applications such as optical and electronic components.
Smart Images

Figure 0007649113000001 
Figure 0007649113000002 
Figure 0007649113000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition that has excellent adhesion when photocured and curable in deep areas, and excellent temporary fixation when photocured. The present invention also relates to an optical component, an electronic component, and an electronic module that use the adhesive composition. [Background technology]
[0002] Adhesive compositions that are cured by irradiation with light and / or heat are used to fix movable parts in camera modules and the like that use imaging elements such as CCDs (charge-coupled devices) and CMOSs (complementary metal-oxide semiconductors). As such adhesive compositions, for example, Patent Document 1 discloses a silicone composition combining specific silicone compounds, and Patent Document 2 discloses a liquid epoxy resin composition combining aminoglycidyl ether, a phenolic curing agent having an alkenyl group, and a thiol compound having a triazine skeleton. However, conventional adhesive compositions have problems such as peeling due to impact, vibration, etc., and displacement of movable parts. In particular, adhesive compositions using radical polymerizable compounds have problems such as warping of the adherend or peeling of the adhesive part due to cure shrinkage, displacement of movable parts, and poor storage stability. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-057755 A [Patent Document 2] JP 2014-031461 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention aims to provide an adhesive composition that is excellent in adhesion when photocured and in deep curing properties, and in temporary fixation when photocured, and also aims to provide an optical component, an electronic component, and an electronic module that use the adhesive composition. [Means for solving the problem]
[0005] The present invention relates to an adhesive composition containing a polymerizable compound, a photopolymerization initiator, and a heat curing agent, and the adhesive composition having a thickness of 800 μm is applied with an adhesive strength of 200 mJ / cm 2 After irradiating the above ultraviolet rays, the cured product A is heated at 80°C or higher for 30 minutes or more. The cured product A is measured at 30°C using the Solid Echo method with pulse NMR. 1 When the free induction decay curve of the spin-spin relaxation of H is waveform-separated into three curves derived from three components, namely, a hard segment (S component), an intermediate segment (M component), and a soft segment (L component), in order of shortest relaxation time, this adhesive composition has a relaxation time of the S component of 0.015 ms or less, a component ratio of the M component of 16% or more, and a component ratio of the L component of 50% or less. The present invention will be described in detail below.
[0006] The present inventors have used pulse NMR to obtain a specific method for the cured product of the adhesive composition. 1 The inventors have investigated the preparation of an adhesive composition in which, when the free induction decay curve of the spin-spin relaxation of H is separated into three components in the order of shortest relaxation time, the hard component (S component), the intermediate component (M component), and the soft component (L component) each satisfy a specific condition. As a result, they have found that an adhesive composition can be obtained that is excellent in adhesion during photothermal curing, deep curing property, and temporary fixation during photocuring, and have completed the present invention.
[0007] The adhesive composition of the present invention has an adhesive strength of 200 mJ / cm2 when applied to a thickness of 800 μm. 2After irradiating the above ultraviolet rays, the cured product A is heated at 80°C or higher for 30 minutes or more. The cured product A is measured at 30°C using the Solid Echo method with pulse NMR. 1 When the free induction decay curve of the spin-spin relaxation of H is separated into three curves derived from the three components of the hard segment (S component), the intermediate segment (M component), and the soft segment (L component) in order of the shortest relaxation time, the relaxation time of the S component is 0.015 ms or less. When the relaxation time of the S component in the cured product A is 0.015 ms or less, the adhesive composition of the present invention has excellent adhesive strength during photothermal curing. The preferred upper limit of the relaxation time of the S component in the cured product A is 0.012 ms, and the more preferred upper limit is 0.011 ms. Although there is no particular preferred lower limit for the relaxation time of the S component in the cured product A, the substantial lower limit is 0.009 ms.
[0008] The measurement by the Solid Echo method using pulsed NMR can be carried out, for example, as follows. 500 mg of the above cured product A or the cured product B described below is introduced into a glass sample tube with a diameter of 10 mm (manufactured by BRUKER, product number 1824511, 10 mm diameter, 180 mm length, flat bottom). Next, the sample tube is placed in a pulse NMR device (manufactured by BRUKER, "the minispec mq20") and held at 30°C for 10 minutes, after which a Solid Echo method is performed at 30°C. 1 The free induction decay curve of the spin-spin relaxation of H is separated into three curves derived from the three components, S, M, and L. The waveform separation is performed by fitting using both Gaussian and exponential types. The analysis software "TD-NMRA (Version 4.3 Rev 0.8)" manufactured by BRUKER is used, and fitting is performed using a Gaussian type for the S component and an exponential type for the M and L components, according to the product manual. For the analysis, fitting is performed using points up to 0.5 msec on the relaxation curve. The following equation is used for fitting: Y = A1 × exp(-1÷w1 × (t÷T2A) w1 )+B1×exp(-1÷w2×(t÷T2B) w2 )+C1×exp(-1÷w3×(t÷T2C) w3 ) Here, w1 to w3 are Weibull coefficients, w1 is 2, and w2 and w3 are 1. A1 is the component ratio of the S component, B1 is the component ratio of the M component, and C1 is the component ratio of the L component, and T2A is the relaxation time of the S component, T2B is the relaxation time of the M component, and T2C is the relaxation time of the L component. t is time. Furthermore, for the Solid Echo method, the following settings are made: Scans: 128 times (set the number of scans to obtain a fitting relaxation curve depending on the amount of hardened material A or B) Recycle Deray: 1sec (or 5x T1) Acquisition scale: 1 ms
[0009] The above cured product A was prepared by applying the adhesive composition to a PET film to a thickness of 800 μm, and then layering another PET film on top of it, and applying 200 mJ / cm 2 After irradiating with ultraviolet light of 1000 mJ / cm or more, the film can be heated at 80°C or more for 30 minutes or more. The preferable lower limit of the ultraviolet light amount is 800 mJ / cm. 2 There is no particular upper limit for the amount of ultraviolet light, but the practical upper limit is 100,000 mJ / cm 2 It is.
[0010] Generally, when measured by pulsed NMR, 1 A free induction decay curve of spin-spin relaxation of H is obtained. The obtained free induction decay curve can be separated into three curves derived from the three components S, M, and L components in the order of shortest relaxation time. That is, the measured free induction decay curve is a superposition of the free induction decay curves derived from the three components S, M, and L. Such a method of separating and analyzing into three components using pulse NMR is well known, and examples of documents in which this method is described include JP 2018-2983 A and the like. The S component is a component with a short relaxation time in pulsed NMR measurement, and is a hard component with low molecular mobility. On the other hand, the L component is a component with a long relaxation time in pulsed NMR measurement, and is a soft component with high molecular mobility. The M component has a relaxation time in pulsed NMR measurement between the S component and the L component, and therefore its molecular mobility is also between the S component and the L component.
[0011] In the adhesive composition of the present invention, the relaxation time of the M component in the cured product A is preferably 0.018 ms at the lower limit and 0.050 ms at the upper limit. When the relaxation time of the M component in the cured product A is within this range, the cured product has a moderate flexibility and does not easily break. The more preferable lower limit of the relaxation time of the M component in the cured product A is 0.020 ms, and the more preferable upper limit is 0.048 ms.
[0012] In the adhesive composition of the present invention, the component ratio of the M component in the cured product A is 16% or more. By having the component ratio of the M component in the cured product A be 16% or more, the adhesive composition of the present invention can have a strong adhesive strength due to the presence of a certain amount of softening components. The preferred lower limit of the component ratio of the M component in the cured product A is 17%, and the more preferred lower limit is 18%. Although there is no particular preferred upper limit for the component ratio of component M in the cured product A, the substantial upper limit is 40%.
[0013] In the adhesive composition of the present invention, the component ratio of the L component in the cured product A is 50% or less. By having the component ratio of the L component in the cured product A be 50% or less, the cured product of the adhesive composition of the present invention can have high deep curing properties and can firmly hold the adherend. The upper limit of the component L ratio in the cured product A is preferably 46%, and more preferably 43%. The substantial lower limit of the component L ratio in the cured product A is 0.3%, and the preferred lower limit is 1%.
[0014] In the adhesive composition of the present invention, the component ratio of the S component in the cured product A is preferably 25% at the lower limit and 82% at the upper limit. When the component ratio of the S component in the cured product A is 25% or more, the adhesive composition of the present invention can appropriately adjust the adhesive strength for firmly fixing the adherend. When the component ratio of the S component in the cured product A is 82% or less, the adhesive composition of the present invention can appropriately adjust the flexibility of the cured product so that it does not easily crack. A more preferable lower limit of the component ratio of the S component in the cured product A is 30%, and a more preferable upper limit is 80%.
[0015] The adhesive composition of the present invention has an adhesive strength of 1000 mJ / cm2 when applied to a thickness of 800 μm. 2 The cured product B obtained by irradiating the ultraviolet light was measured at 30°C using a pulse NMR with a Solid Echo method. 1 The preferred lower limit of the S component ratio in the free induction decay curve of the spin-spin relaxation of H is 7%, and the preferred upper limit is 43%. When the S component ratio in the cured product B is 7% or more, the holding power of the obtained cured product to the adherend can be made sufficient. When the S component ratio in the cured product B is 43% or less, the adhesive composition of the present invention has a superior temporary holding power required for correcting the position of the adherend after temporary fixing. The more preferred lower limit of the S component ratio in the cured product B is 10%, and the more preferred upper limit is 41%. The above cured product B was prepared by applying the adhesive composition to a PET film to a thickness of 800 μm, and then layering another PET film on top of it, and applying 1000 mJ / cm 2 It can be obtained by irradiating the film with ultraviolet light of 1000 nm.
[0016] The relaxation times of the S component and the M component in the cured product A, the component ratios of the S component, the M component, and the L component in the cured product A, and the component ratio of the S component in the cured product B can be set within the above-mentioned ranges by adjusting the types and content ratios of each component constituting the adhesive composition.
[0017] The adhesive composition of the present invention contains a polymerizable compound. The polymerizable compound preferably contains a radically polymerizable compound having no epoxy group and a compound having an epoxy group.
[0018] The radically polymerizable compound having no epoxy group preferably contains a (meth)acrylic compound and a cyclic amide compound having a vinyl group. In this specification, the term "(meth)acrylic" means acrylic or methacrylic, the term "(meth)acrylic compound" means a compound having a (meth)acryloyl group, and the term "(meth)acryloyl" means acryloyl or methacryloyl. Furthermore, an amide compound having a (meth)acryloyl group and a cyclic structure is treated as the above-mentioned (meth)acrylic compound, not as the above-mentioned cyclic amide compound having a vinyl group.
[0019] Examples of the (meth)acrylic compound include (meth)acrylic acid ester compounds, epoxy (meth)acrylates, and (meth)acrylamide compounds. In this specification, the term "(meth)acrylate" means acrylate or methacrylate, and the term "epoxy (meth)acrylate" refers to a compound in which all epoxy groups in an epoxy compound have been reacted with (meth)acrylic acid.
[0020] Examples of the monofunctional (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, and the like. Sil (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, tetrahydrofurfuryl alcohol acrylic acid polymer ester, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-Octafluoropentyl (meth)acrylate, Imido (meth)acrylate, Dimethylaminoethyl (meth)acrylate, Diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 2-(((butylamino)carbonyl)oxy)ethyl (meth)acrylate, (3-propyloxetan-3-yl)methyl (meth)acrylate, (3-butyloxetan-3-yl)methyl (meth)acrylate, (3-ethyloxetan-3-yl)ethyl (meth)acrylate , (3-ethyloxetan-3-yl)propyl (meth)acrylate, (3-ethyloxetan-3-yl)butyl (meth)acrylate, (3-ethyloxetan-3-yl)pentyl (meth)acrylate, (3-ethyloxetan-3-yl)hexyl (meth)acrylate, γ-butyrolactone (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-isobutyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-cyclohexyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, and cyclic trimethylolpropane formal acrylate.
[0021] Examples of the bifunctional (meth)acrylic acid ester compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate. Examples of the di(meth)acrylate include neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, and tricyclodecane dimethanol di(meth)acrylate.
[0022] In addition, examples of the (meth)acrylic acid ester compounds having three or more functional groups include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0023] Examples of the epoxy (meth)acrylate include bisphenol A type epoxy (meth)acrylate, bisphenol F type epoxy (meth)acrylate, bisphenol E type epoxy (meth)acrylate, and caprolactone modified versions of these.
[0024] Examples of the (meth)acrylamide compound include N,N-dimethyl(meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N,N-dimethylaminopropyl(meth)acrylamide.
[0025] The preferred lower limit of the content of the (meth)acrylic compound in 100 parts by weight of the polymerizable compound is 15 parts by weight, and the preferred upper limit is 60 parts by weight. When the content of the (meth)acrylic compound is 15 parts by weight or more, the adhesive composition obtained is cured well by ultraviolet light, and the temporary fixation property is superior. When the content of the (meth)acrylic compound is 60 parts by weight or less, the hardness of the adhesive composition obtained after ultraviolet light curing can be made soft to a certain degree, and the ease of position correction after temporary fixation is superior. The more preferred lower limit of the content of the (meth)acrylic compound is 25 parts by weight, and the more preferred upper limit is 40 parts by weight.
[0026] Examples of the cyclic amide compound having a vinyl group include compounds represented by the following formula (1).
[0027] [ka]
[0028] In the formula (1), n represents an integer of 2 to 6.
[0029] Examples of the compound represented by the above formula (1) include N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, etc. Among these, N-vinyl-ε-caprolactam is preferred.
[0030] The content of the cyclic amide compound having a vinyl group in 100 parts by weight of the polymerizable compound is preferably 15 parts by weight at the lower limit, and 50 parts by weight at the upper limit. By setting the content of the cyclic amide compound having a vinyl group within the above range, the adhesive composition obtained has better deep curing properties. The content of the cyclic amide compound having a vinyl group is more preferably 25 parts by weight at the lower limit, and 40 parts by weight at the upper limit.
[0031] Examples of the compound having an epoxy group include bisphenol A type epoxy compounds, bisphenol E type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, bisphenol O type epoxy compounds, 2,2'-diallyl bisphenol A type epoxy compounds, alicyclic epoxy compounds, hydrogenated bisphenol type epoxy compounds, propylene oxide-added bisphenol A type epoxy compounds, resorcinol type epoxy compounds, biphenyl type epoxy compounds, sulfide type epoxy compounds, diphenyl ether type epoxy compounds, dicyclopentadiene type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, ortho-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthalene phenol novolac type epoxy compounds, glycidyl amine type epoxy compounds, alkyl polyol type epoxy compounds, rubber-modified type epoxy compounds, and glycidyl ester compounds.
[0032] The compound having an epoxy group preferably includes a compound having an epoxy group and a radically polymerizable group. Examples of the compound having an epoxy group and a radically polymerizable group include a (meth)acrylic acid ester having a glycidyl group, a partially (meth)acrylic modified epoxy compound, and the like. In this specification, the above-mentioned "partially (meth)acrylic modified epoxy compound" means a compound having one or more epoxy groups and one or more (meth)acryloyl groups in one molecule, which is obtained by reacting a portion of the epoxy group of an epoxy compound having two or more epoxy groups in one molecule with (meth)acrylic acid.
[0033] Examples of the (meth)acrylic acid ester having a glycidyl group include glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate glycidyl ether, 2-hydroxypropyl (meth)acrylate glycidyl ether, 3-hydroxypropyl (meth)acrylate glycidyl ether, 4-hydroxybutyl (meth)acrylate glycidyl ether, and polyethylene glycol-polypropylene glycol (meth)acrylate glycidyl ether.
[0034] Examples of the partially (meth)acrylic modified epoxy compound include partially (meth)acrylic modified bisphenol A type epoxy compounds, partially (meth)acrylic modified bisphenol F type epoxy compounds, partially (meth)acrylic modified bisphenol E type epoxy compounds, and the like.
[0035] When the adhesive composition of the present invention is used in a portion requiring an alignment step, the adhesive composition of the present invention preferably contains a compound having an epoxy group and a (meth)acryloyl group as the compound having an epoxy group and a radical polymerizable group. The "alignment step" may be, for example, an active alignment step in a camera module.
[0036] The preferred lower limit of the content of the compound having an epoxy group in 100 parts by weight of the polymerizable compound is 10 parts by weight, and the preferred upper limit is 50 parts by weight. When the content of the compound having an epoxy group is 10 parts by weight or more, the adhesive composition obtained has better adhesive strength after thermal curing. When the content of the compound having an epoxy group is 50 parts by weight or less, the adhesive composition obtained does not inhibit photocurability and has better adhesive strength after thermal curing. The more preferred lower limit of the content of the compound having an epoxy group is 20 parts by weight, and the more preferred upper limit is 40 parts by weight.
[0037] The preferred lower limit of the total content of the compounds having a radical polymerizable group in 100 parts by weight of the polymerizable compound is 45 parts by weight, and the preferred upper limit is 90 parts by weight. When the total content of the compounds having a radical polymerizable group is 45 parts by weight or more, the adhesive composition obtained is cured well by ultraviolet light, and the temporary fixation property is more excellent. When the total content of the compounds having a radical polymerizable group is 90 parts by weight or less, the hardness of the adhesive composition obtained after ultraviolet light curing can be made soft to a certain extent, and the ease of position correction after temporary fixation is more excellent. The more preferred lower limit of the total content of the compounds having a radical polymerizable group is 55 parts by weight, and the more preferred upper limit is 70 parts by weight. In this specification, the "total content of compounds having a radical polymerizable group" means the total content of the radical polymerizable compound not having an epoxy group and the compound having an epoxy group and a radical polymerizable group when the polymerizable compound includes the radical polymerizable compound not having an epoxy group and the compound having an epoxy group and a radical polymerizable group.
[0038] The adhesive composition of the present invention contains a photopolymerization initiator. As the photopolymerization initiator, a photoradical polymerization initiator is suitably used.
[0039] Examples of the photoradical polymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone compounds.
[0040] Specific examples of the photoradical polymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-(dimethylamino)-1-(4-(morpholino)phenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinyl)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethan-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2- Examples of such benzoin include methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propan-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether.
[0041] The content of the photopolymerization initiator is preferably 0.1 parts by weight at the lower limit and 5 parts by weight at the upper limit with respect to 100 parts by weight of the polymerizable compound. By the content of the photopolymerization initiator being within this range, the adhesive composition obtained has excellent storage stability and excellent photocurability. The more preferred lower limit of the content of the photopolymerization initiator is 0.2 parts by weight, the more preferred upper limit is 3 parts by weight, the even more preferred lower limit is 0.3 parts by weight, the even more preferred upper limit is 2.5 parts by weight, the particularly preferred lower limit is 0.5 parts by weight, and the particularly preferred upper limit is 2 parts by weight.
[0042] The adhesive composition of the present invention may contain a thermal polymerization initiator in addition to the above-mentioned photopolymerization initiator. As the thermal polymerization initiator, a thermal radical polymerization initiator is preferably used.
[0043] Examples of the thermal radical polymerization initiator include those composed of an azo compound, an organic peroxide, etc. Among them, an initiator composed of an azo compound (hereinafter also referred to as an "azo initiator") is preferable. The azo compound may, for example, have a structure in which a plurality of units such as polyalkylene oxide or polydimethylsiloxane are bonded via an azo group. As the polymeric azo compound having a structure in which a plurality of units such as polyalkylene oxide are bonded via the azo group, those having a polyethylene oxide structure are preferred. Specific examples of the azo compound include a polycondensate of 4,4'-azobis(4-cyanopentanoic acid) and polyalkylene glycol, and a polycondensate of 4,4'-azobis(4-cyanopentanoic acid) and polydimethylsiloxane having a terminal amino group.
[0044] Examples of the organic peroxide include ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, peroxy esters, diacyl peroxides, and peroxydicarbonates.
[0045] The content of the thermal polymerization initiator is preferably 0.1 parts by weight at the lower limit and 10 parts by weight at the upper limit, relative to 100 parts by weight of the polymerizable compound. By setting the content of the thermal polymerization initiator within this range, the adhesive composition obtained has excellent storage stability and excellent thermosetting properties. The more preferred lower limit of the content of the thermal polymerization initiator is 0.2 parts by weight, the more preferred upper limit is 7 parts by weight, the even more preferred lower limit is 0.3 parts by weight, the even more preferred upper limit is 5 parts by weight, the particularly preferred lower limit is 0.5 parts by weight, and the particularly preferred upper limit is 1 part by weight.
[0046] The adhesive composition of the present invention contains a heat curing agent. The heat curing agent preferably has a melting point of 100° C. or less. When the heat curing agent has a melting point of 100° C. or less, the adhesive composition of the present invention has excellent curing properties when heated at low temperatures. The heat curing agent more preferably has a melting point of 80° C. or less.
[0047] The heat curing agent preferably includes a heat curing agent having a lowest initiation zone temperature of 80° C. or less. By using a heat curing agent having a lowest initiation zone temperature of 80° C. or less, the adhesive composition of the present invention has superior low-temperature curing properties. The heat curing agent more preferably has a lowest initiation zone temperature of 79° C. or less, and even more preferably has a lowest initiation zone temperature of 78° C. or less. From the viewpoint of storage stability, the heat curing agent preferably has a lowest initiation zone temperature of 70° C. or higher. The above-mentioned "lowest value of the initiation region temperature" can be measured by differential scanning calorimetry (DSC) as the reaction initiation temperature when 100 parts by weight of bisphenol A type epoxy resin and 5 parts by weight of the above-mentioned heat curing agent are mixed and heated at a rate of 5°C / min.
[0048] Examples of the heat curing agent include imidazole curing agents, amine curing agents, etc. Among them, it is preferable to use an imidazole curing agent having the lowest initiation zone temperature of 80° C. or less.
[0049] Examples of the imidazole-based curing agent include imidazole, 2-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzylimidazole, 1-benzyl-2-phenylimidazole, and 1-cyanoethyl-2-methylimidazole. Examples of the imidazole curing agent having the lowest initiation zone temperature of 80° C. or less include 2-methylimidazole (initiation zone temperature 76° C. to 92° C.) and 1-benzyl-2-methylimidazole (initiation zone temperature 79° C. to 106° C.).
[0050] Examples of the amine curing agent include trimethylamine, triethylamine, N,N-dimethylpiperazine, triethylenediamine, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4.0)-undecene-7, and 1,5-diazabicyclo(4,3.0)-nonene-5.
[0051] The content of the heat curing agent is preferably 0.1 parts by weight at the lower limit and 7 parts by weight at the upper limit, based on 100 parts by weight of the polymerizable compound. By setting the content of the heat curing agent within this range, the adhesive composition obtained has excellent heat curing properties while maintaining excellent storage stability. The more preferred lower limit of the content of the heat curing agent is 0.2 parts by weight, the more preferred upper limit is 5 parts by weight, the even more preferred lower limit is 0.3 parts by weight, the even more preferred upper limit is 4 parts by weight, the particularly preferred lower limit is 0.5 parts by weight, and the particularly preferred upper limit is 3 parts by weight.
[0052] The adhesive composition of the present invention preferably contains a filler for the purposes of improving viscosity, further improving adhesion due to a stress dispersion effect, improving the linear expansion coefficient, and the like.
[0053] As the filler, an inorganic filler or an organic filler can be used. Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, alumina, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate. Examples of the organic filler include polyester fine particles, polyurethane fine particles, vinyl polymer fine particles, and acrylic polymer fine particles. In particular, the filler preferably contains silica whose surface has been methylated. By using the silica whose surface has been methylated as the filler, the adhesive composition obtained has excellent adhesion and the thixotropic index described below can be easily adjusted.
[0054] The preferred lower limit of the content of the filler in 100 parts by weight of the adhesive composition of the present invention is 0.1 parts by weight, and the preferred upper limit is 70 parts by weight. By having the content of the filler in this range, it is possible to suppress deterioration of the coating property, etc., while more effectively improving the adhesiveness, etc. The more preferred lower limit of the content of the filler is 5.0 parts by weight, and the more preferred upper limit is 50 parts by weight. The content of the filler is preferably 5 parts by weight at the lower limit and 50 parts by weight at the upper limit with respect to 100 parts by weight of the polymerizable compound. By setting the content of the filler within this range, the effect of improving adhesion and the like can be more effectively exhibited while suppressing deterioration of coating properties and the like. The more preferred lower limit of the content of the filler is 10 parts by weight, and the more preferred upper limit is 40 parts by weight.
[0055] The adhesive composition of the present invention may contain the above-mentioned light-shielding agent. By containing the above-mentioned light-shielding agent, the adhesive composition of the present invention can be suitably used as a light-shielding adhesive.
[0056] Examples of the light-shielding agent include iron oxide, titanium black, aniline black, cyanine black, fullerene, carbon black, resin-coated carbon black, etc. Among these, titanium black is preferable. The above light-shielding agents may be used alone or in combination of two or more kinds.
[0057] The titanium black is a substance that has a higher transmittance for light in the ultraviolet region, particularly for light with a wavelength of 370 nm or more and 450 nm or less, compared to the average transmittance for light with a wavelength of 300 nm or more and 800 nm or less. That is, the titanium black is a light-shielding agent that imparts light-shielding properties to the adhesive composition of the present invention by sufficiently blocking light with wavelengths in the visible light region, while allowing light with wavelengths in the ultraviolet region to pass through. As the light-shielding agent, a substance with high insulating properties is preferred, and titanium black is also suitable as a light-shielding agent with high insulating properties.
[0058] Although the titanium black exhibits sufficient effects even when not surface-treated, it is also possible to use titanium black whose surface has been treated with an organic component such as a coupling agent, or titanium black whose surface has been coated with an inorganic component such as silicon oxide, titanium oxide, germanium oxide, aluminum oxide, zirconium oxide, magnesium oxide, etc. Among these, titanium black treated with an organic component is preferred in that it can further improve insulation properties.
[0059] Among the titanium blacks mentioned above, commercially available titanium blacks include, for example, titanium black manufactured by Mitsubishi Materials Corporation and titanium black manufactured by Ako Kasei Co., Ltd. Examples of the titanium black manufactured by Mitsubishi Materials Corporation include 12S, 13M, 13M-C, 13R-N, and 14M-C. An example of the titanium black manufactured by Ako Kasei Co., Ltd. is Tilac D.
[0060] The preferred lower limit of the specific surface area of the titanium black is 13 m 2 / g, with a preferred upper limit of 30m 2 / g, and a more preferable lower limit is 15m 2 / g, with a more preferable upper limit of 25m 2 / g. The volume resistivity of the titanium black preferably has a lower limit of 0.5 Ω·cm and a higher limit of 3 Ω·cm, more preferably a lower limit of 1 Ω·cm and a more preferably upper limit of 2.5 Ω·cm.
[0061] The primary particle diameter of the light-shielding agent is preferably 1 nm in lower limit and 5000 nm in upper limit. By making the primary particle diameter of the light-shielding agent within this range, the obtained adhesive composition can have better light-shielding properties. The primary particle diameter of the light-shielding agent is more preferably 5 nm in lower limit and 200 nm in upper limit, still more preferably 10 nm in lower limit and still more preferably 100 nm in upper limit. The primary particle size of the light-shielding agent can be measured by dispersing the light-shielding agent in a solvent (water, organic solvent, etc.) using NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).
[0062] The preferred lower limit of the content of the light-shielding agent in 100 parts by weight of the adhesive composition of the present invention is 0.2 parts by weight, and the preferred upper limit is 5 parts by weight. By having the content of the light-shielding agent in this range, the adhesive composition obtained has excellent effects of improving the light-shielding property while suppressing deterioration in adhesion, strength after curing, and drawability. The more preferred lower limit of the content of the light-shielding agent is 0.5 parts by weight, and the more preferred upper limit is 3 parts by weight.
[0063] The adhesive composition of the present invention may contain a silane coupling agent for the purpose of further improving adhesiveness.
[0064] As the silane coupling agent, for example, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, and the like are suitably used.
[0065] The preferred lower limit of the content of the silane coupling agent in 100 parts by weight of the adhesive composition of the present invention is 0.1 parts by weight, and the preferred upper limit is 5.0 parts by weight. By the content of the silane coupling agent being within this range, it is possible to more effectively improve the adhesiveness while suppressing bleeding out, etc. The more preferred lower limit of the content of the silane coupling agent is 0.3 parts by weight, and the more preferred upper limit is 3.0 parts by weight.
[0066] The adhesive composition of the present invention may contain a viscosity modifier for the purposes of improving the short-term wettability onto an adherend and shape retention. Examples of the viscosity modifier include fumed silica and layered silicates. The viscosity modifiers may be used alone or in combination of two or more kinds.
[0067] The preferred lower limit of the content of the viscosity modifier in 100 parts by weight of the adhesive composition of the present invention is 0.5 parts by weight, and the preferred upper limit is 20 parts by weight. By having the content of the viscosity modifier in this range, the adhesive composition can be more excellent in the effects of improving the short-term application and shape retention of the adherend. The more preferred lower limit of the content of the viscosity modifier is 1.0 part by weight, and the more preferred upper limit is 10 parts by weight.
[0068] The adhesive composition of the present invention preferably contains conductive particles. By containing the conductive particles, the adhesive composition of the present invention can be suitably used as a conductive paste or the like.
[0069] The conductive particles may be metal balls, resin fine particles having a conductive metal layer formed on the surface thereof, etc. Among them, resin fine particles having a conductive metal layer formed on the surface thereof are preferable because the excellent elasticity of the resin fine particles allows conductive connection without damaging a transparent substrate, etc.
[0070] The preferred lower limit of the content of the conductive particles in 100 parts by weight of the adhesive composition of the present invention is 0.1 parts by weight, and the preferred upper limit is 20 parts by weight. By having the content of the conductive particles in this range, it is possible to suppress deterioration of the coating property, etc., while more effectively improving the conductivity. The more preferred lower limit of the content of the conductive particles is 1.0 parts by weight, and the more preferred upper limit is 15.0 parts by weight.
[0071] The adhesive composition of the present invention may further contain a crosslinking agent, an organic solvent, a plasticizer, a dispersant, a pigment, etc., within the scope of not impairing the object of the present invention.
[0072] Examples of the crosslinking agent include halohydrin compounds, halogen compounds, isocyanate compounds, bisacrylamide compounds, urea compounds, guanidine compounds, dicarboxylic acid compounds, unsaturated carboxylic acid compounds, unsaturated carboxylic acid ester compounds, and aldehyde compounds. Examples of the halohydrin compound include epichlorohydrin and epibromohydrin. Examples of the halogen compounds include 1,2-dichloroethane and 1,3-dichloropropane. The isocyanate compound may, for example, be hexamethylene diisocyanate. Examples of the bisacrylamide compound include N,N'-methylenebisacrylamide, N,N'-ethylenebisacrylamide, and the like. Examples of the urea compound include urea and thiourea. Examples of the guanidine compound include guanidine and diguanide. Examples of the dicarboxylic acid compound include oxalic acid and adipic acid. Examples of the unsaturated carboxylic acid compound include acrylic acid and methacrylic acid. Examples of the unsaturated carboxylate ester compound include methyl acrylate, methyl methacrylate, 2-ethylhexyl acrylate, isobutyl acrylate, butyl acrylate, 2-ethylhexyl methacrylate, isobutyl methacrylate, and butyl methacrylate. Examples of the aldehyde compound include glyoxal, glutaraldehyde, malonaldehyde, succinaldehyde, adipic aldehyde, phthalaldehyde, isophthalaldehyde, and terephthalaldehyde. These may be used alone or in combination of two or more. If necessary, these crosslinking agents may be dissolved in an organic solvent such as water or alcohol before use.
[0073] Examples of the organic solvent include ketones, alcohols, aromatic hydrocarbons, esters, methyl cellosolve, ethyl cellosolve, butyl cellosolve, terpineol, dihydroterpineol, butyl cellosolve acetate, butyl carbitol acetate, terpineol acetate, and dihydroterpineol acetate. Examples of the ketones include acetone, methyl ethyl ketone, dipropyl ketone, and diisobutyl ketone. Examples of the alcohols include methanol, ethanol, isopropanol, and butanol. Examples of the aromatic hydrocarbons include toluene and xylene. Examples of the esters include methyl propionate, ethyl propionate, butyl propionate, methyl butanoate, ethyl butanoate, butyl butanoate, methyl pentanoate, ethyl pentanoate, butyl pentanoate, methyl hexanoate, ethyl hexanoate, butyl hexanoate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate.
[0074] The adhesive composition of the present invention preferably does not contain the organic solvent, but if it does contain the organic solvent, the preferred upper limit of the organic solvent content is 10.0 wt %. By keeping the organic solvent content at 10.0 wt % or less, curing inhibition is less likely to occur.
[0075] An example of a method for producing the adhesive composition of the present invention is a method in which a polymerizable compound, a photopolymerization initiator, a heat curing agent, and a filler or other agent added as necessary are mixed using a mixer. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer.
[0076] The thixotropic index of the adhesive composition of the present invention is preferably 3.0 at the lower limit and 7.0 at the upper limit. By setting the thixotropic index within this range, the adhesive composition obtained can be applied to a suitable height, and the effect of preventing displacement of movable parts is more excellent. The thixotropic index is more preferably 4.0 at the lower limit and 6.0 at the upper limit. In this specification, the "thixotropic index" refers to the value obtained by dividing the viscosity measured using an E-type viscometer at 25°C and 0.5 rpm by the viscosity measured at 25°C and 5.0 rpm.
[0077] The adhesive composition of the present invention preferably has a cure shrinkage rate of 3% or less. By having the cure shrinkage rate of 3% or less, the adhesive composition of the present invention has an excellent effect of suppressing warping of the adherend or peeling of the bonded portion and preventing displacement of movable parts, and is suitable for use in fixing movable parts. The cure shrinkage rate is more preferably 2.7% or less. Further, although there is no particular preferred lower limit for the cure shrinkage rate, the substantial lower limit is 1%. In this specification, the "cure shrinkage rate" is calculated by dividing the specific gravity of the adhesive composition at 25°C before curing by G A , the specific gravity of the cured adhesive composition at 25°C is G B When it is set, the value is calculated by the following formula. Curing shrinkage rate (%) = ((G B -G A ) / G B ) x 100 The cured product used to measure the specific gravity was prepared by irradiating the adhesive composition with ultraviolet light having a wavelength of 365 nm at 1000 mJ / cm 2 After irradiation, the film can be obtained by heating at 80° C. for 1 hour.
[0078] The adhesive composition of the present invention is suitably used for fixing moving parts, and may be used for fixing metal parts of moving parts, or may be used for fixing non-metal parts of moving parts. Examples of the metal constituting the metal portion include copper and nickel. Examples of non-metallic materials constituting the non-metallic portion include polyamide, polyphenylene sulfide, polycarbonate, LCP (liquid crystal polymer), and ceramics.
[0079] The adhesive composition of the present invention can be cured by irradiation with light. The method of the light irradiation is not particularly limited, and examples thereof include a method of irradiating light using an ultraviolet irradiator such as a metal halide lamp, an LED, a high-pressure mercury lamp, or a chemical lamp. The light irradiation dose in the above light irradiation is 200 mJ / cm 2 The light irradiation dose is preferably 200 mJ / cm or more. 2 By setting the amount to the above, the adhesive composition of the present invention can be sufficiently cured by light irradiation. There is no particular upper limit to the amount of light irradiation, but the preferred upper limit is 10,000 mJ / cm. 2 It is. The illuminance of the light irradiation is not particularly limited, but the preferred lower limit is 10 mW / cm 2 and the preferred upper limit is 2000 mW / cm 2 The illuminance of the light irradiation is 10 mW / cm 2 By setting the irradiation illuminance at 2000 mW / cm or more, the ultraviolet light can reach deeper portions, and the deep portion curing property can be improved. 2 By setting the content to the range below, the photopolymerization product can be cured without decreasing the molecular weight, and the adhesive strength can be further improved.
[0080] The adhesive composition of the present invention can be suitably used for fixing movable parts that require an alignment step in which temporary fixing is performed by light irradiation. The above-mentioned "alignment step" may be, for example, an active alignment step in the case of a camera module.
[0081] Furthermore, an optical component having a cured product of the adhesive composition of the present invention, and an electronic component having a cured product of the adhesive composition of the present invention are also each part of the present invention. Furthermore, an electronic module having the optical component of the present invention or the electronic component of the present invention also constitutes the present invention.
[0082] Examples of the electronic module of the present invention include a camera module and a display module. Of these, a camera module is preferred. That is, the adhesive composition of the present invention is preferably used as an adhesive for a camera module. Specific examples of the camera module include those having a cured product of the adhesive composition of the present invention between a substrate and an imaging element such as a CCD or CMOS, between a substrate and a cut filter, between a substrate and a housing, between a cut filter and a housing, or between a housing and a lens unit. Effect of the Invention
[0083] According to the present invention, it is possible to provide an adhesive composition that is excellent in adhesion during photothermal curing, deep curing property, and temporary fixation during photocuring. Also, according to the present invention, it is possible to provide an optical component, an electronic component, and an electronic module that use the adhesive composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0084] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0085] (Examples 1 to 7, Comparative Examples 1 and 2) The materials were mixed in a mixer according to the compounding ratios shown in Tables 1 and 2 to obtain adhesive compositions of Examples 1 to 7 and Comparative Examples 1 and 2. The mixer used was an ARE-310 (manufactured by Thinky Corporation). The materials used in Tables 1 and 2 are as follows: 2-(((butylamino)carbonyl)oxy)ethyl (meth)acrylate: H-ABEI (Osaka Organic Chemical Industry Co., Ltd.) 2-Phenoxyethyl acrylate: Viscoat #192 (Osaka Organic Chemical Industry Co., Ltd.) Isodecyl acrylate: IDAA (Osaka Organic Chemical Industry Co., Ltd.) (3-Ethyloxetan-3-yl)methyl acrylate: OXE-10 (Osaka Organic Chemical Industry Co., Ltd.) N-Acryloylmorpholine: ACMO (KJ Chemicals) Tricyclodecane dimethanol diacrylate: IRR 214-K (manufactured by Daicel Allnex) Isobornyl acrylate: Light acrylate IB-XA (Kyoeisha Chemical Co., Ltd.) N-vinyl-ε-caprolactam: NVC (Tokyo Chemical Industry Co., Ltd.) Propylene oxide-added bisphenol A type epoxy resin: EP-4003S (ADEKA) Bisphenol F type epoxy resin: EXA-830CRP (DIC Corporation) Partially acrylic modified bisphenol A type epoxy resin: UVACURE 1561 (manufactured by Daicel Allnex) Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide: Omnirad 819 (manufactured by iGM resins) 2,4,6-Trimethylbenzoyldiphenylphosphine oxide: Omnirad TPO (manufactured by iGM resins) 2-Methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one: Omnirad 907 (manufactured by iGM resins) 1-Hydroxycyclohexyl phenyl ketone: Omnirad 184 (iGM resins) 2-(Dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinyl)phenyl)-1-butanone: Omnirad 379 (manufactured by iGM resins) 2-Methylimidazole: Curezol 2MZ-H (manufactured by Shikoku Chemical Industries, Ltd.) Polyamine hardener: ADEKA Hardener EH-5057PK (ADEKA) 3-Glycidoxypropyltrimethoxysilane: Sila-Ace S-510 (manufactured by Chisso Corporation) 3-Methacryloxypropyltrimethoxysilane: KBM-503 (Shin-Etsu Chemical Co., Ltd.) Fused silica: Sunseal SSP-07M (Tokuyama) Fumed silica 1: AEROSIL RY200S (manufactured by Nippon Aerosil Co., Ltd.) Fumed silica 2: AEROSIL RX200 (manufactured by Nippon Aerosil Co., Ltd.) Titanium Black: 13M-C (Mitsubishi Materials)
[0086] (Pulse NMR measurement) Each adhesive composition obtained in the Examples and Comparative Examples was applied to a PET film to a thickness of 800 μm, and then another PET film was placed on top of it. The resulting laminate was then subjected to an irradiation of 1000 mJ / cm 2 After irradiation with ultraviolet light, the mixture was heated at 80° C. or higher for 30 minutes or more to obtain a cured product A. In addition, the adhesive composition was applied to a PET film to a thickness of 800 μm, and then another PET film was placed on top of it, and the resulting laminate was subjected to an irradiation of 1000 mJ / cm 2 By irradiating the coated film with ultraviolet light, a cured product B was obtained. The obtained cured products A and B were measured at 30°C using pulse NMR by the Solid Echo method. 1 The free induction decay curve of the spin-spin relaxation of H was separated into three curves derived from the three components of the hard segment (S component), the middle segment (M component), and the soft segment (L component) in the order of shortest relaxation time. The relaxation times of the S component and the M component in the cured product A, the component ratios of the S component, the M component and the L component in the cured product A, and the component ratio of the S component in the cured product B were calculated. The results are shown in Tables 1 and 2. The measurement by the Solid Echo method using the pulsed NMR was carried out as follows. 500 mg of the above-mentioned cured product A or cured product B was introduced into a glass sample tube (manufactured by BRUKER, product number 1824511, 10 mm in diameter, 180 mm in length, flat bottom) with a diameter of 10 mm. The sample tube was placed in a pulsed NMR apparatus (BRUKER's "the minispec mq20"), held at 30 °C for 10 minutes, and then the Solid Echo method was performed at 30 °C. The obtained 1 free induction decay curve of the spin-spin relaxation of 1 H was waveform-separated into three curves derived from three components: the S component, the M component, and the L component. The waveform separation was performed by fitting using both a Gaussian type and an exponential type. For the analysis software "TD-NMRA (Version 4.3 Rev 0.8)" manufactured by BRUKER, according to the product manual, the S component was fitted with a Gaussian type, and the M component and the L component were fitted with an exponential type. Also, for the analysis, fitting was performed using the points up to 0.5 msec of the relaxation curve. In addition, the following formula was used for fitting. Y = A1 × exp(-1 ÷ w1 × (t ÷ T2A) w1 ) + B1 × exp(-1 ÷ w2 × (t ÷ T2B) w2 ) + C1 × exp(-1 ÷ w3 × (t ÷ T2C) w3 ) Here, w1 to w3 are Weibull coefficients, w1 takes a value of 2, and w2 and w3 take a value of 1. A1 is the component ratio of the S component, B1 is the component ratio of the M component, C1 is the component ratio of the L component, T2A is the relaxation time of the S component, T2B is the relaxation time of the M component, and T2C is the relaxation time of the L component. t is time. <Setting conditions of the Solid Echo method> Scans: 128 times Recycle Deray: 1 sec (or 5 times the value of T1) Acquisition scale: 1 ms
[0087] <Evaluation> The following evaluations were performed on each adhesive composition obtained in the examples and comparative examples. The results are shown in Tables 1 and 2.
[0088] (Adhesiveness when photothermally cured) Each adhesive composition obtained in the Examples and Comparative Examples was applied to a liquid crystal polymer (manufactured by Nippon Test Panel Co., Ltd., "Sumika Super LCP E4008") having a length of 100 mm, width of 25 mm, and thickness of 2.0 mm as a substrate, and a silicon wafer substrate (length 2 mm, width 2 mm, thickness 0.7 mm) was placed on top of it. Then, 1000 mJ / cm 2 The adhesive composition was photocured by irradiating it with ultraviolet light (wavelength 365 nm) and then heated at 80°C for 1 hour to obtain a test piece. The die shear strength of the obtained test piece was measured at a speed of 300 μm / s and 25°C using a die shear tester. The bond tester used was a DAGE4000 (manufactured by NORDSON DAGE). The adhesion during photothermal curing was evaluated as follows: when the die shear strength was 65N or more, it was marked "◎", when it was 60N or more but less than 65N, it was marked "○", when it was 50N or more but less than 60N, it was marked "△", and when it was less than 50N, it was marked "×".
[0089] (deep hardening) Each of the adhesive compositions obtained in the Examples and Comparative Examples was filled into a black polycarbonate container having a hole with a diameter of 3 mm, and then 1000 mJ / cm2 was applied in the direction of the hole. 2 The cured depth from the surface of the adhesive composition was measured using a vernier caliper. Deep curing was evaluated as follows: when the cure depth was 1.5 mm or more, it was marked "◎", when it was 600 μm or more and less than 1.5 mm, it was marked "○", when it was 300 μm or more and less than 600 μm, it was marked "△", and when it was less than 300 μm, it was marked "×".
[0090] (Temporary fixation when light-cured) Each adhesive composition obtained in the Examples and Comparative Examples was applied to a liquid crystal polymer ("Sumika Super LCP E4008" manufactured by Nippon Test Panel Co., Ltd.) with a length of 100 mm, width of 25 mm and thickness of 2.0 mm as a substrate, so as to have a length of 10 mm and a width of 1 mm, and a SUS substrate (length of 10 mm, width of 1.5 mm, thickness of 10 mm) was placed on top of the substrate. Then, 1000 mJ / cm was applied from one of the longitudinal sides. 2The adhesive composition was cured by irradiating ultraviolet light (wavelength 365 nm) to obtain a test piece. The die shear strength of the obtained test piece was measured at a speed of 300 μm / s at 25° C. using a die shear tester. The die shear tester used was a bond tester DAGE4000 (manufactured by NORDSON DAGE). The temporary fixation during light curing was evaluated as follows: when the die shear strength was 2N or more and less than 5N, it was marked "◎", when it was 0.8N or more and less than 2N, it was marked "○", when it was 5N or more, it was marked "△", and when it was less than 0.8N, it was marked "×".
[0091] [Table 1]
[0092] [Table 2] [Industrial Applicability]
[0093] According to the present invention, it is possible to provide an adhesive composition that is excellent in adhesion during photothermal curing, deep curing property, and temporary fixation during photocuring. Also, according to the present invention, it is possible to provide an optical component, an electronic component, and an electronic module that use the adhesive composition.
Claims
1. An adhesive composition comprising a polymerizable compound, a photopolymerization initiator, and a heat curing agent, The polymerizable compound includes a radical polymerizable compound having no epoxy group and a compound having an epoxy group, the radical polymerizable compound having no epoxy group includes a (meth)acrylic compound and a cyclic amide compound having a vinyl group, the content of the (meth)acrylic compound is 15 parts by weight or more and 60 parts by weight or less, the content of the cyclic amide compound having a vinyl group is 15 parts by weight or more and 50 parts by weight or less, and the content of the compound having an epoxy group is 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the polymerizable compound; 200 mJ / cm2 to the adhesive composition having a thickness of 800 μm 2 After irradiating the above ultraviolet rays, the cured product A is heated at 80° C. or higher for 30 minutes or more, and the cured product A is measured at 30° C. using a pulse NMR by the Solid Echo method. 1 When the free induction decay curve of the spin-spin relaxation of H is separated into three curves derived from three components, namely, a hard segment (S component), an intermediate segment (M component), and a soft segment (L component), in the order of shortest relaxation time, the relaxation time of the S component is 0.015 ms or less, the component ratio of the M component is 16% or more, and the component ratio of the L component is 50% or less.
1. An adhesive composition comprising:
2. The component ratio of the S component in the cured product A is 25% or more and 82% or less, and the adhesive composition having a thickness of 800 μm is applied with a curing rate of 1000 mJ / cm 2 The cured product B obtained by irradiating the product with ultraviolet light of 100 nm was measured at 30° C. using a pulse NMR with a Solid Echo method. 1 2. The adhesive composition according to claim 1, wherein the ratio of the S component in a free induction decay curve of H spin-spin relaxation is 7% or more and 43% or less.
3. 3. The adhesive composition according to claim 1, wherein the cyclic amide compound having a vinyl group is N-vinyl-ε-caprolactam.
4. 4. The adhesive composition according to claim 1, wherein the compound having an epoxy group includes a compound having an epoxy group and a radically polymerizable group.
5. 5. The adhesive composition according to claim 1, wherein the total content of the compounds having a radical polymerizable group is 45 parts by weight or more and 90 parts by weight or less in 100 parts by weight of the polymerizable compound.
6. 6. The adhesive composition according to claim 1, 2, 3, 4 or 5, which is used for fixing moving parts.
7. An optical part comprising a cured product of the adhesive composition according to claim 1 , 2 , 3 , 4 , 5 or 6 .
8. An electronic part having a cured product of the adhesive composition according to claim 1 , 2 , 3 , 4 , 5 , or 6 .
9. An electronic module comprising an optical component according to claim 7 or an electronic component according to claim 8.
Citation Information
Patent Citations
Method and composition for bonding components to glass
JP1999502542A
Preparation of surface decorative member
JP2000328010A
Silicone composition and cured product thereof
JP2011057755A
Moisture-curable polyurethane hot-melt adhesive and decorative fixture member
JP2013043914A
Liquid epoxy resin composition and composite member as well as electronic component device
JP2014031461A